Yield and Fruit Quality of Banana Musa (AAB) Nendran as Influenced by Nutrient Sources - Meghwal, Manohar Lal; Jyothi, M. L.; Pushpalatha, P. B.; Bhaskar, Jyothi (International Journal of Bio-resource and Stress Management, 2021)
The present study was conducted at Banana Research Station, Kannara, Kerala Agricultural University Thrissur, Kerala, India during 2017-2018. Evaluation was conducted by raising the crop under different manurial combinations. Banana yield and fruit quality characters were found to be influenced by the different treatments. Analysis was conducted for the biochemical constituents of mature and ripe Nendran banana fruits. Maximum starch (99.61 mg), protein (5.53 mg), crude fibre (3.95%) and tannin content (0.81 g) in mature fruits were obtained in Treatment-8 (FYM @ 29 kg, lime @ 0.5 kg and wood ash @ 4 kg plant-1 as basal dose+fertigation with extract of 14 kg FYM till one month after bunch emergence, once in four days+in situ green manuring). This treatment also recorded lowest titrable acidity (0.38%), highest β-carotene content (595.67 µg) in ripe banana fruits. Maximum TSS content (26.23 obrix) was obtained in Treatment-6 in which fertilizers applied as modified package of practices (POP) recommendation of KAU as per soil test). Maximum yield (160.88 kg plot-1) and fruit quality parameters; maximum total sugars (17.55%) and reducing sugars (11.38%), sugars/acid ratio (45.07) of ripe banana fruits were obtained in Treatment-3 where 15 kg FYM and 0.5 kg lime as basal+Poultry manure @ 14 kg plant-1+ash @ 4 kg plant-1 applied in two splits i.e. one as basal and one 3 MAP+in situ green manuring practised. It was evident from the study that application of organic manures improved fruit quality characters in Nendran banana.